Asas Itikad Baik Sebagai Upaya Perlindungan Hukum terhadap Pelaku Usaha Dalam Pembiayaan Konsumen (Studi Putusan Mahkamah Agung Republik Indonesia Nomor 1041 K/Pdt.Sus-BPSK/2017) - Arfi Azhari; Siti Nurbaiti (Jurnal Hukum Adigama, 2019)
Consumer Finance is a financing activity for the procurement of goods based on consumer needs with payment in installments. In consumer financing, the parties must have good intentions for the smooth running of the agreement, but in practice the principle of good faith is often violated by the parties such as in the Decision of the Supreme Court of the Republic of Indonesia No. 1041 / K-Pdt.Sus-BPSK/2017 decides to grant a request from Martha Sitorus (consumer) with consideration of Article 2 of the UUPK and the principle of good faith, which in this case with the existence of the decision clearly has harmed PT. Toyota Astra Financial Service Medan (business actor) for consumer financing agreements. The problem studied is how the legal protection of business actors carried out by consumers in consumer financing and how the RI Decision No. 1041 / K-Pdt.Sus-BPSK/2017 towards legal protection of business actors carried out by consumers in consumer financing. The research method used is a normative method supported by interview data. The results of the writing illustrate that the business actor does not receive legal protection as stipulated in Article 6 letter (b) UUPK and in the Decision of the Supreme Court of the Republic of Indonesia No. 1041 / K-Pdt.Sus-BPSK/2017 The Panel of Judges is not right in making decisions.